Denosumab: an investigational drug for the management of postmenopausal osteoporosis - E Michael Lewiecki (Dove Medical Press, 2008)
E Michael LewieckiNew Mexico Clinical Research & Osteoporosis Center, Albuquerque, New Mexico, USAAbstract: Denosumab (AMG 162) is an investigational fully human monoclonal antibody with a high affinity and specificity for receptor activator of nuclear factor-κB ligand (RANKL), a cytokine member of the tumor necrosis factor family. RANKL, the principal mediator of osteoclastic bone resorption, plays a major role in the pathogenesis of postmenopausal osteoporosis and other skeletal disorders associated with bone loss. Denosumab inhibits the action of RANKL, thereby reducing the differentiation, activity, and survival of osteoclasts, and lowering the rate of bone resorption. Clinical trials have shown that denosumab increases bone mineral density (BMD) and reduces bone turnover in postmenopausal women with low BMD. Studies to evaluate the fracture risk benefit and long-term safety of denosumab in women with postmenopausal osteoporosis (PMO) are ongoing. Denosumab is a potential treatment for PMO and other skeletal disorders.Keywords: osteoporosis, treatment, denosumab, AMG 162, RANKL, OPG